Decoding the genetic blueprints of neurological disorders: disease mechanisms and breakthrough gene therapies - Saeed, Umar; Piracha, Zahra Zahid; Tariq, Muhammad Nouman; Syed, Shayan; Rauf, Maria; Razaq, Laiba; Iftikhar, Muhammad Kaleem; Maqsood, Amna; Ahsan, Syed Muhammad (Frontiers in Neurology, 2025)
Neurological disorders pose a rapidly growing global health burden, significantly affecting cognitive and motor functions with profound societal repercussions. This comprehensive review probe into the genetic foundations of various neurological conditions while exploring innovative RNA-based therapeutics particularly gene therapies as cutting edge treatment strategies. Through an in-depth analysis of existing literature, the study examines the genetic landscape, disease mechanisms, and gene-based intervention possibilities across a range of neurological disorders, including Cerebellar Ataxias, Autosomal Recessive Ataxia, Mitochondrial Cerebellar Ataxia, Multiple System Atrophy (MSA), Idiopathic Late-Onset Cerebellar Ataxia, Hereditary Spastic Paraplegias, Alzheimer’s Disease, Vascular Dementia, Lewy Body Dementia, Frontotemporal Dementias, Inherited Prion Diseases, and Huntington’s Disease. It uncovers the intricate network of genetic mutations driving these disorders, shedding light on their mechanisms and uncovering promising therapeutic targets. The review also highlights the remarkable potential of RNA-based therapeutics, with gene therapies standing at the forefront of precision treatment approaches. By offering an up-to-date understanding of the genetic intricacies and emerging therapeutic possibilities in neurological disorders, this study significantly contributes to the advancement of precision medicine in neurology. It also paves the way for future research and clinical applications aimed at improving patient care and outcomes.